2015
DOI: 10.1186/s12917-015-0396-7
|View full text |Cite
|
Sign up to set email alerts
|

Serological prevalence of viral agents that induce reproductive failure in South Korean wild boar

Abstract: BackgroundViral agents associated with reproductive failure such as Aujeszky’s disease virus (ADV), encephalomyocarditis virus (EMCV), and porcine parvovirus (PPV) have also been identified in European wild boar. To screen for the presence of antibodies against ADV, EMCV, and PPV from wild boar (Sus scrofa) in South Korea, 481 serum samples were collected from wild boar hunted between December 2010 and May 2011.ResultsOf the 481 serum samples tested, 47 (9.8%) and 37 (7.7%) were seropositive for ADV and EMCV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The virus can agglutinate chicken, guinea pig, mouse, human, monkey, rat, and cat erythrocytes. Thus, hemagglutination inhibition assays (HAI) were developed relatively early [ 64 , 80 ] and they are still used in research and practice in some countries [ 5 , 44 , 81 , 82 ]. Other serological methods like the serum neutralization (SN) assay or the modified direct complement-fixation (MDCF) test were also utilized earlier, but today the enzyme-linked immunosorbent assay (ELISA) is the most frequently applied test to detect PPV-specific antibodies.…”
Section: Detection and Isolation Of Ppvmentioning
confidence: 99%
“…The virus can agglutinate chicken, guinea pig, mouse, human, monkey, rat, and cat erythrocytes. Thus, hemagglutination inhibition assays (HAI) were developed relatively early [ 64 , 80 ] and they are still used in research and practice in some countries [ 5 , 44 , 81 , 82 ]. Other serological methods like the serum neutralization (SN) assay or the modified direct complement-fixation (MDCF) test were also utilized earlier, but today the enzyme-linked immunosorbent assay (ELISA) is the most frequently applied test to detect PPV-specific antibodies.…”
Section: Detection and Isolation Of Ppvmentioning
confidence: 99%
“…Serologic evidence of exposure to Aujeszky's disease virus, encephalomyocarditis virus and porcine parvovirus in wild boar was reported in one study (Jeoung et al, 2015). Notifiable diseases or pathogens for which published evidence was reported in wild boar include Aujeszky's disease, porcine respiratory and reproductive syndrome, classical swine fever and Trichinella spp., which could result in trade embargoes if diagnosed in domestic swine (Choi et al, 2012;Jeoung et al, 2015;Kim et al, 2011;Seo, Sunwoo, Hyun, & Lyoo, 2012). Consequently, the risk of wild boar acting as reservoirs for these diseases of swine production and these pathogens spilling over into domestic swine farms appears to be a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Although not many countries have searched for PPV in wild boars, one study reported that 44 of 842 wild boars sampled in the Transylvania region of Romania between 2006 and 2011 were positive for PPV [16]. In addition, of the 481 wild boars captured in South Korea from 2010-2011, 29% were seropositive for antibodies against PPV (142/481) [17]. Interestingly, a GenBank search suggested that only PPV1, PPV2, and PPV7 have been detected in Korean domestic pigs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, of the 481 wild boars captured in South Korea from 2010-2011, 29% were seropositive for antibodies against PPV (142/481) [17]. Interestingly, a GenBank search suggested that only PPV1, PPV2, and PPV7 have been detected in Korean domestic pigs [17].…”
Section: Introductionmentioning
confidence: 99%